2011
DOI: 10.1080/13501763.2011.615194
|View full text |Cite
|
Sign up to set email alerts
|

Not so intergovernmental after all? On democracy and integration in European Foreign and Security Policy

Abstract: The status of democracy in European foreign and security policy is increasingly questioned. In order to identify if there is something at the European Union (EU) level that requires legitimation, we need to establish whether there has been a move beyond intergovernmentalism. In this contribution an analytical scheme that makes it possible to identify such a move and its putative democratic implications is developed. Four constituent pillars of intergovernmentalism are identified and discussed. These pertain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 29 publications
2
43
0
2
Order By: Relevance
“…Our study also adds to existing scholarship on deliberation in EU policy and decision-making (Eriksen, 2009(Eriksen, , 2014Eriksen & Fossum, 2012;Joerges, 2001;Sjursen, 2011;Stie, 2013).…”
Section: Conclusion and Precautionsmentioning
confidence: 65%
“…Our study also adds to existing scholarship on deliberation in EU policy and decision-making (Eriksen, 2009(Eriksen, , 2014Eriksen & Fossum, 2012;Joerges, 2001;Sjursen, 2011;Stie, 2013).…”
Section: Conclusion and Precautionsmentioning
confidence: 65%
“…A systematic empirical investigation of CFSP/CSDP outputs (Bicchi 2011(Bicchi : 1128Sjursen 2011Sjursen : 1086, based on 138 questionnaires and 37 interviews, has revealed that conflicting states interests very frequently lead to decisions which resemble LCD logics and/or the positions of the most powerful states. Consequentialist practices are still largely present in EU foreign policy and often dominate over more social ones.…”
Section: Resultsmentioning
confidence: 99%
“…6 For an alternative perspective on EU foreign and security policy, see Sjursen (2012), who argues that the EU is capable of rising above mere intergovernmentalism. See also the contributions in Telò & Ponjaert 2013.…”
Section: Notesmentioning
confidence: 99%